2015
DOI: 10.1039/c5ee02616d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical pore-in-pore and wire-in-wire catalysts for rechargeable Zn– and Li–air batteries with ultra-long cycle life and high cell efficiency

Abstract: Inexpensive hierarchical oxygen reduction and oxygen evolution reaction (ORR/OER) catalysts offer higher cell efficiency and much longer cycle life than Pt/C + IrO2 bifunctional catalysts in metal–air batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…34,35 On the other hand, the interconnected hierarchical porous structures with a large pore volume and surface area offer a smooth transport of reactants, as well as the significantly elevated utilization of active sites. 21,22 These synergetic effects as mentioned above are responsible for the high performance of HP-Fe-N/CNFs in electrochemical and Zn-air battery test (vide infra).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…34,35 On the other hand, the interconnected hierarchical porous structures with a large pore volume and surface area offer a smooth transport of reactants, as well as the significantly elevated utilization of active sites. 21,22 These synergetic effects as mentioned above are responsible for the high performance of HP-Fe-N/CNFs in electrochemical and Zn-air battery test (vide infra).…”
Section: Resultsmentioning
confidence: 96%
“…also hide the activities of catalysts. 21 Qiao et al designed a series of ordered meso-/macro porous g-C 3 N 4 /C catalysts and revealed the improved catalytic performance that fast diffusion brings. 22 Combined the advantages of diverse pores, hierarchically marco/meso/micro-porous structures aim at the promoted density and accessibility of active sites was much desired in the catalysts to lifting the catalytic performance Traditional methods for constructing hierarchically porous carbon materials usually employed silica template strategy.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that some Zn–air batteries have used decoupled O 2 electrodes loaded with different electrocatalysts for ORR and OER separately. However, this approach often complicates the battery structures . Thus, bifunctional O 2 electrocatalysts are much more desirable.…”
Section: Air Electrodesmentioning
confidence: 99%
“…Although achieving great development of transition‐metal oxides, the electrocatalytic performance is still unsatisfactory, which is heavily hampered by some important drawbacks and limitations, including the inherent low conductivity and serious aggregation of nanoparticles. Carbon‐based hybrid bifunctional catalyst typically consists of strongly coupled oxide nanomaterials and functionalized carbons are then put forward to overcome that . For example, by a simple electrospinning technique, Prabu et al reported a new bifunctional ORR and OER catalyst, in which, perovskite LaTi 0.65 Fe 0.35 O 3− δ (LTFO) nanoparticles were entangled both at the surface and within the nitrogen‐doped carbon nanorods (NCNRs).…”
Section: Bifunctional Catalystsmentioning
confidence: 99%